2022
DOI: 10.1007/s00289-022-04530-6
|View full text |Cite
|
Sign up to set email alerts
|

Green-synthesized silver nanoparticle coating on paper for antibacterial and antiviral applications

Abstract: The use of active packaging has attracted considerable attention over recent years to prevent and decrease the risk of bacterial and viral infection. Thus, this work aims to develop active packaging using a paper coated with green-synthesized silver nanoparticles (AgNPs). Effects of different silver nitrate (AgNO 3 ) concentrations, viz. 50, 100, 150, and 200 mM (AgNPs-50, AgNPs-100, AgNPs-150, and AgNPs-200, respectively), on green synthesis of AgNPs and coated paper properties were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 63 publications
0
4
1
Order By: Relevance
“…TEM revealed that the AgNPs were spherical and polydispersed (figure 2(A)) with the size distribution of the AgNPs in the range of 5-47 nm and an average size of 23.1 ± 6.8 nm. The size and shape of the AgNPs were significantly different from previous studies [33][34][35][36], probably because of the synthetic conditions including the concentration of AgNO 3 , synthesis temperature, reaction time, and the mangosteen peel extraction procedure. In addition, the shape of the AgNPs was associated with the efficiency of antibacterial activity.…”
Section: Characterisation Of Agnpscontrasting
confidence: 74%
“…TEM revealed that the AgNPs were spherical and polydispersed (figure 2(A)) with the size distribution of the AgNPs in the range of 5-47 nm and an average size of 23.1 ± 6.8 nm. The size and shape of the AgNPs were significantly different from previous studies [33][34][35][36], probably because of the synthetic conditions including the concentration of AgNO 3 , synthesis temperature, reaction time, and the mangosteen peel extraction procedure. In addition, the shape of the AgNPs was associated with the efficiency of antibacterial activity.…”
Section: Characterisation Of Agnpscontrasting
confidence: 74%
“…In general, the higher the Ag content, the stronger the antibacterial activity (Youssef et al., 2019). However, its addition should be controlled to avoid possible food safety risks (Srikhao et al., 2023; Williams et al., 2017). Therefore, a key research focus is to reduce the usage of silver while maintaining the same level of antibacterial efficacy.…”
Section: Types Of Antimicrobial Substancesmentioning
confidence: 99%
“…Ag/TiO 2 NPs can be potentially used as a disinfection coating for paper and to improve its mechanical properties (Lin et al., 2023; Samir et al., 2022). Composite materials, such as conductive polymer–silver nanoparticles (Lai et al., 2022), polymer–silver nanoparticles composite(El Guerraf et al., 2022), organically modified silica (ORMOSIL) physically doped with AgNPs (Trabelsi et al., 2020), and AgNPs integrated with citric acid and ex‐GM 2 (Srikhao et al., 2023), can provide antimicrobial properties to paper through coating techniques. They show remarkably high and stable activity against representative gram‐positive and gram‐negative bacteria.…”
Section: Types Of Antimicrobial Substancesmentioning
confidence: 99%
“…Previous studies reported that the properties of AgNPs combined with TA produced synergistic antibacterial activities by increasing the permeability of the microbial cell membrane 20,62,63 . Furthermore, AgNPs also stimulate the generation of reactive oxygen species for attacking microbial cells and also interrupt the replication of bacterial DNA and the signal transduction pathways in the cells 64 . www.nature.com/scientificreports/ Water absorption of as-prepared plywood by bio-adhesive nanocomposite.…”
Section: Antibacterial and Antifungal Activities Of Bio-adhesive Nano...mentioning
confidence: 99%